(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article scientifically analyzes the role of state policy in the process of digitalization of the economy and its impact on economic development. The main goal of the research is to assess the effectiveness of political, institutional, and organizational measures implemented by the state in the context of the digital economy and to determine their impact on economic growth, competitiveness, and social well-being. The research methodology used methods of system analysis, comparative-statistical methods, study of regulatory legal acts, and comparison of foreign experience. The article highlights the mechanisms for increasing economic efficiency through the development of digital infrastructure, the introduction of an e-government system, and the support of digital finance and e-commerce. The research results show that the consistent and comprehensive implementation of state policy is an important factor in ensuring the sustainable development of the digital economy.